God Steps Back, God Comes Down: Features of God’s Face in the essay: «Implicit Forms of Loving God» by Simone Weil - Caum Aregay, Nuria (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
We focus on the image of God implied by Simone Weil’s essay «Implicit Forms of Loving God». In it, the author points a God that renounces to exert all his power. God steps back when God creates, allowing the existence of something different to him. His absence is a sign of his respectful love. But, at the same time, God comes down, comes close, maintains the initiative in what is supernatural. He founds and inspires our existence. Along with these reflections, the author keeps the tension among the autonomy of creation, the root of evil and God, who is powerful in loving. The search of Simone Weil connects with the theological question of Auschwitz and sheds light on the experience of God’s absence in our context.
Keywords: God’s powerlessness; suffering of God; autonomy of Creation